Female American mink, Mustela vison, mate multiply in a free-choice environment - Thom, MD; Macdonald, D; Mason, G; Pedersen, V; Johnson, P (2004)
Like most solitary carnivores, the home ranges of male American mink overlap with those of several females, but each female typically shares its range with only a single male. Nevertheless, female mink produce multiply sired litters. Unusually among mammals, the physiological characteristics of female American mink make them highly suited to multiple paternity, suggesting that polyandry in the species may result from female behaviour rather than from coercion by males. In a free-choice experiment on captive-bred animals, all female mink mated multiply, with seven of the eight mating with all three available partners. Since females sometimes resisted copulations, multiple mating in this species may result from their behaviour rather than male coercion. Females visited males nonrandomly, but visiting patterns did not predict mating patterns, suggesting disparate social and mating preferences. There was no evidence for precopulatory female choice, since the allocation of copulations among available males did not deviate significantly from the expected distribution. Females mated multiply only around the predicted times of ovulation, contrary to the expectation that they should be more selective at times of peak fertility. Larger males copulated for longer in total: copulation duration is probably under male control, suggesting that larger males could influence mating duration, perhaps increasing their share of paternity by greater sperm transfer. Our observations suggest that in wild populations, mating patterns could be influenced by female preference for multiple partners. © 2004 The Association for the Study of Animal Behaviour. Published by Elsevier Ltd. All rights reserved.